Tinjauan Komprehensif Konsep Uang Taqiyuddin An-Nabhani - Muslich Candrakusuma; Arif Santoso (Universitas Muhammadiyah Ponorogo, 2021)
Money is one of the pillars of the economy. Money facilitates the process of exchanging commodities and services. Every process of production and distribution must use money. Money has the main function as a medium of exchange, and is derived from other functions such as standard of value, store of value, unit of account. According to Taqiyuddin an-Nabhani, Islam has determined a fixed and standard unit of money in a distinctive form, namely gold and silver. Taqiyuddin normatively proves that money in Islam is gold and silver, or the monetary standard is gold and silver. Historically, it has been proven in history that the gold system is the longest-used currency in human history, and its application is always relevant under any circumstances. Meanwhile, politically, Taqiyuddin argued that the switch to the paper money system was a hoax for the purpose of imperialization.